The Political Crisis in Malawi: From Authoritarianism to Democracy - Nsanja, Alinane R. (My University, 2006)
The thesis is a contribution to the existing literature on the democratic process in Malawi with specific focus on two areas namely, the factors that led to the opening up of political space and the implementation of multiparty democracy. The thesis argues that multiparty democracy in Malawi, which transpired due to internal and external factors, had been perceived as the means of transforming the oppressive climate created by the Banda regime. However, despite three multiparty elections since the 1990s, the UDF government, which succeeded Banda, has failed to broaden the avenues for the consolidation of democracy in Malawi, leading to disillusionment among the people. Ten years of multiparty democracy have only resulted in the regression to the practices of the very regime it replaced. Currently Malawi is plagued with a lack of independent media, weak civil society, corruption among top government officials and a weak economy to mention a few. The thesis argues that this is because of the nature of the ruling class as well as the issue of ethnicity, which has resulted in the contestation of power.
Masrer of ArtsInternational Relations
Keywords: Malawi; crisis; democracy; authoritarianism